WISATA HALAL MUSLIM MILENIAL - Iflah, Iflah; Putri, Kinkin Yuliaty Subarsa (Jurnal Common, 2019)
Year to year halal tourism is starting to become popular, in line with the increase in Muslim tourists. Development of halal tourism now carried out by various countries, both majority Muslim and non-Muslim countries. Target of halal tourism market is growing rapidly in the millennial Muslim because it is considered potential in driving halal tourism development. This study of halal tourism seeks to interpret cultural tourism which is synergized with the halal industry as a spiritual experience of modern society, namely millennial Muslims. This literature review will disscuss millennial Muslims in Indonesia as the main segment in utilizing the potential offered from domestic and foreign halal tourism based on literature and other references relating to halal tourism and Y generations. This literature study aims to explore halal tourism at local and abroad which focuses on the segmentation of millennial Muslims as a population that is considered potential in increasing halal tourism development. Focus on study in a particular segmentation is expected to be able to broaden the understanding of the concept of halal tourism from the perspective of the younger generation so that the halal tourism industry is able to develop according to the changes and needs of the times.